Integrating new institutional logics: sustainability and climate action in local government practices in Finland and Indonesia - Busscher, Tim; Vikstedt, Elina; Sinervo, Lotta-Maria; Luhtala, Mika; Laihonen, Harri; Welinder, Olga (Springer, 2025)
International climate and sustainable development policies and initiatives have converged into a distinct institutional logic, which local governments need to integrate into their organizational practices. However, smaller and medium-sized governments often struggle to do so. Given their resource constraints and limited capacity, these government organizations frequently join networks that can serve as platforms for the institutional work required to integrate a new logic. Yet how such networks facilitate or hinder this integration remains largely unexplored. Using a most-different comparative design contrasting a mature Finnish SDG network with Indonesia’s Water as Leverage (WaL) initiative, we examine how network characteristics shape the political, technical, and cultural institutional work needed to integrate the socio-ecological logic into municipal accounting and district-level spatial planning. In Finland, a stable, cohesive network co-produced a ‘model practice’ that municipalities could apply in their organizational practices. In Indonesia, the absence of central coordination and shared interpretive frameworks left institutional work fragmented, and no model practice emerged. Consequently, the socio-ecological logic was only weakly integrated into local practices. These findings demonstrate that networks function not merely as coordination platforms but as social institutions whose carrying capacity—defined by coordination structures, actor alignment, and available resources—critically determines whether institutional work translates into organizational practice change.
Keywords: Institutional logics; institutional work; local governments; organizational practices; accounting; sustainability; climate action; Public Management; Julkisjohtaminen